Developing an integrated model for talent nurturing in Gulf higher education institutions: an analytical foresight approach - Abunaser, Fathi M.; Almustafa, Sarah Saleh (Frontiers in Education, 2026)
This study aims to develop a sustainable, foresight-based model for nurturing university talent in the Gulf Cooperation Council (GCC) countries. The study employs a mixed-methods descriptive–analytical research design, integrating document analysis with expert consultation. It draws on a systematic review and analysis of selected international, Arab, and Gulf experiences in higher education talent development and collects data from a purposive sample of 53 experts working in GCC universities. The experts were purposively selected based on predefined criteria, including academic specialization, professional experience, and active involvement in talent development and excellence initiatives in higher education. The study adopted both quantitative and qualitative descriptive analytical procedures, including thematic analysis, to identify key indicators and practices related to sustainable talent development. The findings highlight the importance of establishing a clear institutional vision for university talent development, supported by an integrated organizational structure and policies that promote early identification of talented students, enhance their academic, research, and leadership capabilities, and ensure continuous evaluation of program outcomes. Analysis of global and regional experiences particularly the “Gifted Community” initiative as an applied Gulf model revealed that integrating talent development programs into university strategic frameworks enhances innovation, research productivity, and the university’s societal impact. Based on these findings, the study developed a proposed foresight-based model structured around the integration of inputs, processes, and outputs. The model is built upon the principles of sustainability, empowerment, and innovation, providing a strategic framework that aligns talent development programs with the needs of academic and societal institutions. This model serves as an institutional guide for Gulf universities to establish a sustainable culture of talent nurturing, support academic excellence, and contribute to building innovation ecosystems in higher education.